Improving Epistemological Beliefs and Moral Judgment Through an STS-Based Science Ethics Education Program. - Han, Hyemin; Jeong, Changwoo (Science & Engineering Ethics, 2014)
This study develops a Science-Technology-Society (STS)-based science ethics education program for high school students majoring in or planning to major in science and engineering. Our education program includes the fields of philosophy, history, sociology and ethics of science and technology, and other STS-related theories. We expected our STS-based science ethics education program to promote students' epistemological beliefs and moral judgment development. These psychological constructs are needed to properly solve complicated moral and social dilemmas in the fields of science and engineering. We applied this program to a group of Korean high school science students gifted in science and engineering. To measure the effects of this program, we used an essay-based qualitative measurement. The results indicate that there was significant development in both epistemological beliefs and moral judgment. In closing, we briefly discuss the need to develop epistemological beliefs and moral judgment using an STS-based science ethics education program.